Improvement of Accuracy in Environmental Dosimetry by TLD Cards Using Three-dimensional Calibration Method - HosseiniAliabadi S. J.; Hosseini Pooya S. M.; Afarideh H.2 , Mianji F. (Journal of Biomedical Physics and Engineering, 2015)
Background: The angular dependency of response for TLD cards may cause deviation from its true value on the results of environmental dosimetry, since TLDs may be exposed to radiation at different angles of incidence from the surrounding area. Objective: A 3D setting of TLD cards has been calibrated isotropically in a standard radiation field to evaluate the improvement of the accuracy of measurement for environmental dosimetry. Method: Three personal TLD cards were rectangularly placed in a cylindrical holder, and calibrated using 1D and 3D calibration methods. Then, the dosimeter has been used simultaneously with a reference instrument in a real radiation field measuring the accumulated dose within a time interval. Result: The results show that the accuracy of measurement has been improved by 6.5% using 3D calibration factor in comparison with that of normal 1D calibration method. Conclusion: This system can be utilized in large scale environmental monitoring with a higher accuracy